Factors affecting successful antituberculosis treatment: a single-center experience - Gonçalves, Marcella Cardoso; de Aguiar, Amanda Aparecida Silva [UNESP]; Biadola, Ana Paula; Mazaro, Paulo José Mascarenhas; Rodrigues, Marcus Vinícius Pimenta; do Prado, Rosana Leal; Peresi-Lordelo, Eliana (FapUNIFESP (SciELO), 2023)
OBJECTIVE: The identification of factors that influence a favorable antituberculosis treatment outcome could be of great use for the promotion of specific health actions to increase the success rate. Thus, the objective of this study was to investigate the factors affecting successful antituberculosis treatment in patients seen at a reference service in the Western region of São Paulo State/Brazil. METHODS: A retrospective study was carried out from 2010 to 2016 based on the data obtained from the Notification Disease Information System of TB patients treated at a reference service in Brazil. The study included patients with treatment outcomes and excluded those from the penitentiary system or with resistant or multidrug-resistant TB. Patients were categorized as having a successful (cured) or unsuccessful (treatment default and death) treatment outcome. The association between TB treatment outcomes and social and clinical factors was analyzed. RESULTS: A total of 356 cases of TB were treated between 2010 and 2016. Among the cases, the majority were cured and the overall treatment success rate was 85.96%, with a range between 80.33% (2010) and 97.65% (2016). After the exclusion of resistant/multidrug-resistant TB, 348 patients were analyzed. In the final logistic regression model analysis, education less than 8 years (OR 1.66; p<0.0001) and people living with human immunodeficiency virus/acquired immunodeficiency syndrome (OR 0.23; p<0.0046) were found to be significantly related to an unfavorable treatment outcome. CONCLUSION: Low education and being a person living with human immunodeficiency virus/acquired immunodeficiency syndrome are vulnerability factors that can affect the successful outcome of antituberculosis treatment.
Keywords: Antitubercular agents; HIV infections; Socioeconomic factors; Tuberculosis